NEW STUDENT REGISTRATION SYSTEM ADMINISTRATION IN SCHOOL-CIPUTAT JUNIOR DARUSSALAM CIMANGGIS BY USING VISUAL BASIC 6.0 - Nurliyana Nurliyana; Aqwam Rosadi Kardian,S.kom.,MMSI (Jurnal Sistem Informasi, 2005)
SLTP Darussalam during this process the data by using the manual method. In this way requires very large data. The author tries to make the new student enrollment administration system using Microsoft Visual Basic 6.0. Visual Basic 6.0 programming language is the quickest and easiest way to make an application in Microsoft Windows. Visual Basic programming easier to interact directly with elements for every form of programming. As a windows based program that Visual Basic has the ability to interact with all Windows applications like Microsoft Word, Excel, Access and so on.